Impact of frailty on perioperative and oncologic outcomes in patients undergoing surgery or ablation for renal cancer: a systematic review - Campi, Riccardo; Berni, A.; Amparore, D.; Bertolo, R.; Capitanio, U.; Carbonara, U.; Erdem, S.; Ingels, A.; Kara, O.; Klatte, T.; Kriegmair, Maximilian; Marchioni, M.; et al. (Minerva urology and nephrology, 2022)
Impact of frailty on perioperative and oncologic outcomes in patients undergoing surgery or ablation for renal cancer: a systematic review